2010
DOI: 10.1017/s1751731110000327
|View full text |Cite
|
Sign up to set email alerts
|

Does the newly weaned piglet select a zinc oxide supplemented feed, when given the choice?

Abstract: animal Does the newly weaned piglet select a zinc oxide supplemented feed, when given the choice? An experiment was conducted to examine whether weaned piglets would display preference for a food containing a pharmacological level of zinc oxide (ZnO). A total of 60 piglets were weaned at 7.8 kg 6 0.14 (s.e.m.) and 27.8 6 0.11 days of age into eight mixed sex groups of seven or eight piglets per pen. Groups were balanced for litter origin, weaning weight and sex. Piglet feeding behaviour was constantly recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The quadratic effect of dietary Zn content on feed intake may relate to the influence of Zn on the palatability of feed. Reynolds et al [ 52 ] found that, when pigs weaned at day 28 were given the choice between a Zn unsupplemented diet and a diet supplemented with 3100 mg Zn/kg (as ZnO), up to 91 % of the total feed consumption was of the unsupplemented diet. Zhang and Guo [ 53 ] and Yin et al [ 54 ] found a higher concentration of circulating ghrelin in pigs (24–28 days of age) fed a 2000 mg Zn/kg diet compared to a 100–130 mg Zn/kg diet.…”
Section: Discussionmentioning
confidence: 99%
“…The quadratic effect of dietary Zn content on feed intake may relate to the influence of Zn on the palatability of feed. Reynolds et al [ 52 ] found that, when pigs weaned at day 28 were given the choice between a Zn unsupplemented diet and a diet supplemented with 3100 mg Zn/kg (as ZnO), up to 91 % of the total feed consumption was of the unsupplemented diet. Zhang and Guo [ 53 ] and Yin et al [ 54 ] found a higher concentration of circulating ghrelin in pigs (24–28 days of age) fed a 2000 mg Zn/kg diet compared to a 100–130 mg Zn/kg diet.…”
Section: Discussionmentioning
confidence: 99%
“…This adverse response of piglets to oral iron supplementation has been previously reported by Svodoba and Drabek [18] as they demonstrated insufficient voluntary intake of inorganic iron supplements that resulted in numerous cases of piglet IDA. Anise has been reported to act as a masking agent [27], which could have suppressed the aversive taste associated with oral iron supplements [34] and standardised creep feed intake across all treatments. The disappearance of creep feed throughout lactation in this study corroborates with the comparable studies [35] as piglets made minimal use of creep feed in the early days of life (100-150 g/day), but this gradually rose to 400 g/day around weaning (day 25 of life).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies proved that dietary supplementation with high levels of ZnO effectively suppressed the growth of E . coli and other coliform bacteria in weaning piglets [ 8 10 ]. However other studies showed adverse effects of high dietary ZnO, such as reducing the numbers of intestinal beneficial bacteria, or increasing environmental zinc emissions [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%